The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5114/amsad.2017.68539
|View full text |Cite
|
Sign up to set email alerts
|

Social, demographic and clinical characteristics of patients suffering from peripheral vascular disease treated surgically compared to patients treated with endovascular angioplasty

Abstract: IntroductionAtherosclerosis is the most common cause of chronic lower limb ischaemia. Many factors that have a crucial influence on the development of the disease, its course and prognosis have been identified. The risk factors seem to be subject to interventions due to their susceptibility to changes. It is important to increase the engagement of doctors and nurses performing the screening oriented on risk factors, medical consultation regarding giving up smoking, changing the diet and undertaking physical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Given that vascular surgery patients are generally older and functionally limited, a consult system that is more easily accessible than the traditional in-person consultation could fill a necessary gap in the care of our patients. 15,16 This study provides utilization, compliance rates, and long-term outcomes after eConsult and shows its relative effectiveness and safety in comparison to current outcomes after traditional consultation. Anecdotally, the patients and providers appreciate this service, given travel times for patients and the directness to the referring physician.…”
Section: Discussionmentioning
confidence: 98%
“…Given that vascular surgery patients are generally older and functionally limited, a consult system that is more easily accessible than the traditional in-person consultation could fill a necessary gap in the care of our patients. 15,16 This study provides utilization, compliance rates, and long-term outcomes after eConsult and shows its relative effectiveness and safety in comparison to current outcomes after traditional consultation. Anecdotally, the patients and providers appreciate this service, given travel times for patients and the directness to the referring physician.…”
Section: Discussionmentioning
confidence: 98%
“…More advanced lower limb ischaemia, rest pain and foot ulcerations were observed significantly more frequently in the group of patients qualified for surgical treatment than in the endovascular group. Additionally, most common concomitant in the operating group were hypertension, diabetes, coronary heart disease and myocardial infarction (Piotrkowska et al, 2017 ). In a self‐study, a third of patients with vascular disease showed two or more concomitant diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Lower education indicates lower awareness of adopting a healthy lifestyle and lower preventive measures such as screening programs or frequent visits to general practitioners [ 30 , 31 ]. Individuals with a low level of education constitute a high-risk population for atherosclerosis, which is attributed to their preferred life-style [ 32 ].…”
Section: Discussionmentioning
confidence: 99%